Temperature-dependent properties of fat in adipose tissue from pork, beef and lamb. Part 2: rheology and texture. Issue 13 (14th June 2022) - Wijarnprecha, Khakhanang; Fuhrmann, Philipp; Gregson, Christopher; Sillick, Matt; Sonwai, Sopark; Rousseau, Dérick
Abstract : Small and large deformation behaviour of back fat from pork/beef/lamb was dominated by the fat phase at room temperature and by the protein network at higher temperature. Our insights help to replicate fat functionality using plant-based materials. Abstract : Matching the texture of fat in plant-based meat alternatives requires an in-depth understanding of the rheology of animal adipose tissue which, to-date, remains under-studied. Here, we characterised the small and large deformation behaviour of back fat from pork, beef, and lamb, with the underlying goal being the establishment of the temperature-dependent structure–function relationship governing the texture and rheology of adipose tissue. The dynamic rheological behaviour of the back fats was characterised via frequency and amplitude sweeps and large amplitude oscillatory strain (LAOS), as well as texture analysis via puncture tests. At 20 °C, prior to heating, the small and large deformation properties of adipose tissue were dominated by the solid fat phase within the adipose cells. Upon heating to 80 °C, with the fat phase molten, the protein network underpinning the structure of the back fats conferred elastic behaviour to the tissues, and the now-molten oil partly leaked from the adipocytes into the surrounding interstitial space. Upon re-cooling, a bicontinuous network of fat crystals and protein contributed to back fat rheology. Large deformation rheology revealed animal species-specific differences. Prior to heating, pork back fat was characterised by soft yielding behaviour while beef and lamb back fat showed abrupt yielding and intra-cycle strain stiffening. Post-heating, lamb showed the highest stiffness, compared to pork and beef, as well as non-linearities in its stress–strain relationship obtained via LAOS. Such fundamental understanding is essential to provide the required insights to replicate the functionality of adipose tissue using plant-based materials.